COMPARISON OF PAPAYA AND GREEN NUTS EXERCISE ON BREAST MILK PRODUCTION IN TELAGASARI PUSKESMAS, KARAWANG REGENCY IN 2022 - Farlikhatun, Lili; Pebriana, Monita (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2023)
Background : Mother's milk (ASI) is the most perfect single food for babies in the first 6 months of growth, without any additional drinks or drinks. any food. Lactagogum is a substance that can increase milk production, which laktagogum is found in papaya and green bean juice. The purpose of the study: to determine the effect of giving papaya fruit and green bean juice to the smoothness of breast milk in nursing mothers at the Telagasari Health Center 2022. The type of research used in this study was an experimental study. The research design is quasi-experimental and one group pre-test and post-test design using a comparison group. The sample of this study was post partum mothers at PKM Telagasari, totaling 40 people. The technique uses a sample using purposive sampling. Data analysis was carried out, namely bivariate analysis using paired t test (paired sample t test). The results of the study: The characteristics of the respondents mostly between the ages of the mothers were almost entirely (30.0%) aged 20-25 years, 26-30 years (17.5%), 31-35 years (52.5%), most of the parity there were 12 the first child (30%), the second child as many as 12 people (30%), the third child as many as 16 people (40%). Education (5%) SD, (25%) SMP, (67.5%) SMA, D3 (2.5%). Most (90%) were mothers who had IMD while (10%) were mothers who were not. Most of the unemployed (80%), employees (5%), civil servants (1), farmers (5%), etc (7.5%). For children age (85%) children 1 month, age 1 month (10%), age 2 months (5%). The amount of breast milk before giving papaya fruit in the intervention group was 588.95 on average. While the average green bean juice is 606.88. There is an effect of giving papaya fruit and green bean juice to the smoothness of breast milk in nursing mothers at PKM Telagasari (p value 0.000 0.05). The conclusion of the study: There is an effect of giving papaya fruit to the smoothness of breast milk in breastfeeding mothers in the Independent Midwife Practice.